Process reengineering in an online gambling organization: an action research application in a portuguese company - Pires, João Miguel Rodrigues (2021)
Online Gambling industry is exponentially growing in this decade and it is facing a significant attention in the literature. This development can be explained by the continuous Information Technologies progress that has been changing people behaviors, promoting new access to social media, gaming and also online gambling. This new trend has been facing constant changes in legal regulations that require an unique agility from organizations to adapt to these new requirements and still remain competitive. Process reengineering unveils the main methodologies and tools to sustain this tenacity to adapt in long-term perspective, by promoting a continuous improvement culture. Lean, as a major player in these methodologies, supports this agility, by implementing processes best practices to thrive this change and achieve competitive advantage. This research objective is to comprehend how these two universes can be connected to reveal how an online gambling organization can redefine its processes to achieve operational excellence and continuous improvement. This research provides a deep understanding how these methodologies previously mentioned can impact positively distinctive industries as online gambling.